Republic of Kosovo Public Sector Revenues : Tax Policies, Tax Evasion, and Tax Gaps - World Bank (Washington, DC, 2015)
Kosovo has a simple tax system and relatively low tax rates. A risky feature of Kosovo’s tax system is the high dependence on border taxes. In 2012, 71 percent of revenue was collected at the border in the form of trade taxes and value added tax (VAT) on imports. Shifting from border to domestic revenue collection is needed. The simple tax system can make it easier for the tax administration of Kosovo (TAK) to adjust direct taxes while encouraging labor market formality. Low domestic revenue collection suggests the presence of large tax gap - the difference between the amount the TAK should collect and the amount it actually does collect. The wider social and economic consequences of tax evasion are high. Finding ways to raise domestic revenue to compensate for the decline in border revenues is going to require actions on a number of fronts. First, strengthening the TAK’s capacity to increase compliance and reduce tax evasion, through judicial means. Second, reducing the informal economy will bring more firms and employees into tax net. Third, efforts can be made to increase revenues through existing taxes. Finally, policies that boost private sector growth, including an improved business climate, will help increase domestic production and therefore tax revenues.